Pengaruh Penerapan Pendekatan Socio-Scientific Issue (SSI) dalam Materi Zat Aditif dan Zat Adiktif terhadap Literasi Sains dan Islam di Kelas VIII MTsN 1 Lumajang - Bilqis Naqiyah Sukmawati; Abdul Rahim (Universitas Garut, 2026)
ABSTRACT This research is motivated by the demands of 21st century education which requires a paradigm shift from mere mastery of material to the development of scientific literacy and higher-order thinking, especially in Islamic-based educational institutions such as Madrasah Tsanawiyah (MTs) which need to align science with spiritual values. This research aims to describe the picture of students' scientific and Islamic literacy before and after learning, analyze the influence of the Socio-Scientific Issue (SSI) approach, and test the effectiveness of the approach on the material of additives and addictive substances in class VIII MTsN 1 Lumajang. The purpose of this research is to determine: (1) the picture of students' scientific literacy and Islamic literacy before learning, (2) the picture of students' scientific literacy and Islamic literacy after learning, (3) the effect of the Socio-Scientific Issue (SSI) approach on students' scientific literacy and Islamic literacy, and (4) the effectiveness of applying the SSI approach in science learning. The research method used is a quantitative approach with a quasi-experimental design using a Non-equivalent Control Group Design. The research population included all 306 students of class VIII MTsN 1 Lumajang, with samples taken through purposive sampling technique, namely class VIII C as the experimental class and class VIII D as the control class, each consisting of 30 students. The data collection instrument was a multiple-choice test (pretest and posttest), and was supported by interviews, observations, and documentation. Data analysis techniques involved descriptive analysis, prerequisite tests (normality and homogeneity), hypothesis testing, and N-Gain tests. The results of the study showed that: (1) the initial abilities of students' scientific literacy and Islamic literacy before learning were in the moderate category with an average pretest score of 72 in the experimental class and the control class; (2) after learning, there was an increase in students' abilities, indicated by an average posttest of 88.17 in the experimental class and 78.33 in the control class; (3) there is a significant influence of the application of the Socio-Scientific Issues (SSI) approach on students' scientific literacy and Islamic literacy, which is proven through an independent sample t-test with a significance value of 0.000 (<0.05) and (4) the application of the SSI approach is quite effective in improving student learning outcomes, which is shown by the N-Gain value of 0.6095 in the moderate category. Keywords: learning outcomes, Islamic literacy, scientific literacy, socio-scientific issues (SSI)